Desarrollo de las unidades morfológicas costeras durante el holoceno en el golfo San José, Chubut, Argentina - Schillizzi, Roberto Antonio (2001)
Morphological characteristics of Ameghino isthmus, Chubut province, Argentina, are described. Spatial relations between geoforms are also defined and endogenetic and exogenetic processes taking place during the Holocene to sculpture the present landscape are analyzed. It is established the presence of morphological units derived from marine and continental actions. It is possible to define a regressive marine process dominant in the region for the last 7000 years BP. In this research, coastal geology, geomorphology and neotectonic domains are introduced as a digression. References of climatic effects that could have acted in the region are also done.